Cultivo comercial de camarones Litopenaeus vannamei en Costa Rica durante el niño 2015: incidencia de enfermedades - Valverde-Moya, José A. (2018)
Production yields of the marine shrimp, Litopenaeus vannamei, cultured in earthen ponds in the Gulf of Nicoya, Costa Rica were studied to evaluate the effect of diseases diagnosed during El Niño 2015 event. Two culture systems on earthen ponds were used: three short cycles (SC) per year in farms with low disease incidence and two long cycles (LC) per year in highly affected farms with high mortality. Survival was low in the 2 CL (35.3 ± 3.2%) as compared to the 3 CC (63.1 ± 3.2%). An inverse relationship between average weight at harvesting and the final culture density was obtained (20.3 ± 0.8 g in 2 CL and 15.2 ± 1.6 g in 3 CC) as well as a growth compensation (1.29 ± 0.12 and 1.08 ± 0.10 g/week in 2 CL and 3 CC, respectively). The final production was directly proportional to the survival, with an average of 717 ± 8 kg/ha in 2 CL and 941 ± 53 kg/ha in 3 CC. The production was reduced to half in the 2 CL (1434 kg/ha*year) with respect to 3 CC (2823 kg/ ha*year). No production benefit was detected by maintaining the culture to achieve larger sizes with survivors following events of severe mortalities.